Serial survey shows community intervention may contribute to increase in knowledge of Tuberculosis in 30 districts of India - Badri Thapa; Banuru Muralidhara Prasad; Sarabjit S. Chadha; Jamie Tonsing (BMC, 2016)
Abstract Background Correct knowledge about Tuberculosis (TB) is essential for appropriate healthcare seeking behaviour and to accessing diagnosis and treatment services timely. There are several factors influencing knowledge about TB. The present study was conducted to assess the change in community knowledge of Tuberculosis (TB) and its association with respondent's socio-demographic characteristics in two serial knowledge-attitude-practice surveys. Methods Community level interventions including community meetings with youth groups, village health committees and self-help groups and through mass media activities were undertaken to create awareness and knowledge about TB and service availability. Increase in knowledge on TB and its association with respondent's socio-demographic characteristics was assessed by two serial KAP surveys in 2010-2011 (baseline) and 2012-2013 (midline) in 30 districts of India. Correct knowledge of TB was assessed by using lead questions and scores were assigned. The composite score was dichotomized into two groups (score 0-6, poor TB knowledge and score 7-13, good TB knowledge). Results In baseline and midline survey, 4562 and 4808 individuals were interviewed. The correct knowledge about TB; cough ≥2 weeks, transmission through air, 6-8 months treatment duration, and free treatment increased by 7 % (p-value <0.05), 11 % (p-value <0.05), 2 % (p-value <0.05), and 8 % (p-value <0.05) in midline compared to baseline, respectively. The knowledge on sputum smear test for diagnosis of TB was 66 % in both surveys while knowledge on availability of free treatment and that TB is curable disease decreased by 5 % and 2 % in midline (p-0.001), compared to baseline, respectively. The mean score for correct knowledge about TB increased from 60 % in baseline to 71 % in midline which is a 11 % increase (p-value <0.001). The misconception regarding on transmission of TB by- sharing of food and clothes and handshake persisted in midline. Respondents residing in northern (OR, 2.2, 95 % CI, 1.7-2.6) and western districts (OR, 3.4, 95 % CI, 2.7-4.1) of India and age groups- 25-34 years (OR, 1.3; 95 % CI, 1.1-1.6) and 45-44 years (OR, 1.4; 95 % CI, 1.1-1.7)- were independently associated with good TB knowledge. Conclusions The knowledge about TB has increased over a period of 2 years and this may be attributable to the community intervention in 30 districts of India. The study offers valuable lesson for designing TB related awareness programmes in India and in other high burden countries.